Public crowdsourcing: Analyzing the role of government feedback on civic digital platforms. (11th January 2022) - Schmidthuber, Lisa; Hilgers, Dennis; Randhawa, Krithika
Abstract: Government organizations increasingly use crowdsourcing platforms to interact with citizens and integrate their requests in designing and delivering public services. Drawing on attribution theory, this study asks how the causal attributions of the government response to a citizen request affect continued participation in crowdsourcing platforms. To test our hypotheses, we use a 7‐year dataset of both online requests from citizens to government and government responses to citizen requests. We focus on citizen requests that are denied by government, and find that the reasoning for denying a request is related with continued participation behavior. Citizens are less willing to collaborate further with government via the platform, when their requests are denied although the locus of causality is with the government. This study contributes to research on the role of responsiveness in digital interaction between citizens and government and highlights the importance of rationale transparency to sustain citizen participation.